Natural Lighting of Studio Apartment with East-Oriented Opening - Aisyah Anindya Putri; Dyah Nurwidyaningrum; Tri Wulan Sari (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Less optimized natural lighting would result in apartment residents being dependent on artificial lighting, thus increasing energy consumption. Building opening orientation considerably influences the natural light intensity. This research aimed to analyze the natural lighting pattern on apartment units with east-oriented opening orientation and determine methods to support the existing condition to be optimized. This research applied the descriptive analysis research method assumed from calculation outcome of the software DIALux. Results indicated a proportion of units in The H-Residence Apartment do not meet the requirements specified by SNI 03 6197-2011, predominantly in the kitchen area. The average light intensity in a day in units with east-oriented opening reached its peak at 08.00 – 09.00 a.m. and decreased towards 16.00 p.m. following the sun path. The light intensity in numerous areas exceeded the requirements significantly. Other factors influencing the natural light distribution are layout and interior element. Several ways to optimize the natural light intensity utilization are adding suitable shading device, using dark-colored interior elements, and considering the sun path in designing building openings.